DNA methylation-independent removable insulator controls chromatin remodeling at the HOXA locus via retinoic acid signaling. (24th October 2016) - Ishihara, Ko; Nakamoto, Masafumi; Nakao, Mitsuyoshi
Abstract: Chromatin insulators partition the genome into functional units to control gene expression, particularly in complex chromosomal regions. The CCCTC-binding factor (CTCF) is an insulator-binding protein that functions in transcriptional regulation and higher-order chromatin formation. Variable CTCF-binding sites have been identified to be cell type-specific partly due to differential DNA methylation. Here, we show that DNA methylation-independent removable CTCF insulator is responsible for retinoic acid (RA)-mediated higher-order chromatin remodeling in the human HOXA gene locus. Detailed chromatin analysis characterized multiple CTCF-enriched sites and RA-responsive enhancers at this locus. These regulatory elements and transcriptionally silent HOXA genes are closely positioned under basal conditions. Notably, upon RA signaling, the RAR/RXR transcription factor induced loss of adjacent CTCF binding and changed the higher-order chromatin conformation of the overall locus. Targeted disruption of a CTCF site by genome editing with zinc finger nucleases and CRISPR/Cas9 system showed that the site is required for chromatin conformations that maintain the initial associations among insulators, enhancers and promoters. The results indicate that the initial chromatin conformation affects subsequent RA-induced HOXA gene activation. Our study uncovers that a removable insulator spatiotemporally switches higher-order chromatin and multiple gene activities via cooperation of CTCF and key transcription factors.